Telmisartan improves absolute walking distance and endothelial function in patients with peripheral artery disease - Zankl, Alexandra R.; Ivandic, Boris; Andrassy, Martin; Volz, Hans Christian; Krumsdorf, Ulrike; Blessing, Erwin; Katus, Hugo; Tiefenbacher, Christiane (Clinical research in cardiology, 2010)
Peripheral artery disease (PAD) is associated with high cardiovascular mortality and a poor quality of life. The AT1-receptor blocker telmisartan has been shown to have pleiotropic effects and it may also improve endothelial function. The aim of this study was to analyze the effects of telmisartan on absolute walking distance (WD) and endothelial function in patients with PAD.